National Mining Hall of Fame to Honor Four (Society for Mining, Metallurgy & Exploration, 2007)
Ceremonies for the induction of four mining industry pioneers into the National Mining Hall of Fame will be held Saturday, Sept. 22, 2007 at the Charles F. Barber Pavilion (Museum Convention Center) in Leadville, CO. The four inductees are James Harold Courtright (1908-1986), Dr. Howard L. Hartman (1924-2002), Charles Washington Merrill (1869-1956) and Kenyon E. Richard (1915-1993). The inductions will bring to 197 the number of mining “greats” whose engraved photographs and biographical sketches are installed in the National Mining Hall of Fame.